2022
DOI: 10.3389/fpsyg.2022.901730
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Interpersonal Proximity Evaluation in the COVID-19 Era: Evidence From the Affective Priming Task

Abstract: Social proximity has since ever been evaluated as positive. However, the outbreak of the COVID-19 pandemic has dramatically reduced our social relations to avoid spreading the contagion. The present study aims to investigate people's current assessment of social proximity by using an affective priming paradigm (APP). We hypothesized that if our evaluation of social proximity is positive, then words with positive valence (e.g., relaxed) should be processed faster when preceded by images of social proximity than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Most importantly, it is here shown that spontaneous categorization processes are triggered, grouping individuals as a function of their mask-related behaviors. The implementation of preventive behaviors has become an integral part of people's daily lives, and much has already been done to highlight the possible effects on socio-cognitive processes 9,[52][53][54][55][56][57] . Although there is a widespread hope that we could soon overcome the Covid-19 pandemic, there is still uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, it is here shown that spontaneous categorization processes are triggered, grouping individuals as a function of their mask-related behaviors. The implementation of preventive behaviors has become an integral part of people's daily lives, and much has already been done to highlight the possible effects on socio-cognitive processes 9,[52][53][54][55][56][57] . Although there is a widespread hope that we could soon overcome the Covid-19 pandemic, there is still uncertainty about the future.…”
Section: Discussionmentioning
confidence: 99%
“…It is divided into dimensions such as temporal, spatial, and social viewpoints, or theoretical ( Liberman and Trope, 2014 ). Scerrati et al (2022) demonstrated that the pandemic likely drives the results of individual differences in the assessment of social proximity. Our study focuses on the “social distance” dimension, such as the distance between oneself and others.…”
Section: Discussionmentioning
confidence: 99%